DAMPAK PERCEIVED ORGANIZATIONAL SUPPORT DAN SELF EFFICACY PADA ORGANIZATIONAL CITIZENSHIP BEHAVIOR SERTA PERAN MEDIASI ORGANIZATIONAL COMMITMENT (Studi Pegawai Satpol PP Kota Pasuruan) - Nur Ulifa; Nasharuddin Mas; Rahayu Puji Suci (Bajang Institute, 2023)
The purpose of this study was to obtain empirical evidence about the ability of perceived organizational support and self-efficacy in encouraging an increase in organizational citizenship behavior, either directly or through the mediation of organizational commitment. This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 86 municipal police officers in Pasuruan City. Empirical findings show that perceived organizational support is not capable of driving an increase in OCB, but is capable of organizational commitment. Likewise, self-efficacy is able to encourage an increase in OCB, but it is not able to increase organizational commitment. The mediating role of organizational commitment is quite strong in the effect of perceived organizational support on OCB, but is unable to play a strong role in the effect of self-efficacy on OCB.